501 Can the provision of a home help service for the elderly population reduce the incidence of fall-related injuries?. (1st September 2016) - Bonander, Carl; Gustavsson, Johanna; Nilson, Finn
Abstract : Background: Fall-related injuries are a global public health problem, especially in elderly populations. In this study, the effect of an intervention aimed at reducing the risk of falls in the homes of community-dwelling elderly persons was evaluated. The intervention, which involves home hazards reduction by providing a minor home help service, is provided in the majority of Swedish municipalities. Methods: Intention-to-treat effect estimates were derived using quasi-experimental time series intervention (ITS) analysis for immediate effects and a difference-in-discontinuity (RD) design for long term effects, and community-level estimates were pooled using meta-analysis. The outcome measure was the incidence of fall-related hospitalizations in the treatment population, the age of which varied by municipality (≥65 years, ≥67 years, ≥70 years or ≥75 years). Results: We found no statistically significant reductions in injury incidence in the ITS (IRR 1.01 [95% CI: 0.98–1.05]) or RD (IRR 1.00 [95% CI: 0.97–1.03]) analyses. The results are robust to several different model specifications, including segmented panel regression analysis with linear trend change and community fixed effects parameters. Conclusions: It is unclear whether absence of an effect is due to a low efficacy of the home hazards modifications provided, or a result of low utilisation. Additional studies of the effects on other quality of life measures are recommended before conclusions are drawn regarding the cost-effectiveness of the provision of home help services.